Optimization of solvent systems for color fractionation of monascus pigment - Nur Fathin Shamirah, Daud; Farhan, Mohd Said; M. A., Mokhtar (Universiti Malaysia Pahang, 2023)
Monascus fungi are unique among the various microorganisms that produce edible pigments, which consist of red, orange, and yellow. These pigments are typically present in a mixture. Hence, pigment separation is needed. This study aims to optimize solvent systems that can effectively fractionate the pigments. The optimization was carried out using column chromatography and the data was analyzed using Central Composite Design (CCD). The interaction of the solvent systems ethyl acetate : formic acid : acetic acid : water was optimized. The optimal solvent system obtained was 98 : 14 : 12 : 28 (vol/vol.) for ethyl acetate : formic acid : acetic acid : water, respectively. The red and yellow pigment obtained were 2.42 mg and 0.93 mg, respectively. Based on the finding, 72.2% of the total Monascus pigments was red while remaining was yellow.